Designing Computer Network Subnetting with School Objects Using Cisco Packet Tracer 6.1 - putri, desak putu sekar merta; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
The internet is one part that can not be released in human life today. Every year internet users both in Indonesia and in the world have increased. This increase in internet users causes the availability of IP to decrease. That is because users who will use the internet must have an IP. The availability of IPv4 is currently decreasing. To overcome these problems, IPv6 was made which was announced to replace the existence of IPv4. But another solution that can be taken is using subnetting. With subnetting, IP can be used optimally according to the needs of the host or can make efficient use of IP. And subnetting also functions to avoid congestion resulting from too many hosts on the physical network. And to connect between subnets, routing will be done.